Kant's Notion of Human Dignity in Dialogue with Islamic Thinking: For an Interstitial and Extra-National Account of Human Dignity - Scaglia, Lara (Studia Kantiana, 2023)
Public international law is concerned with the relationship between human dignity and human rights. Concepts such as person, freedom and justice occur in legal texts, often without an accurate definition. To solve these ambiguities, thus contributing to developing a virtuous legal and political debate, a philosophical clarification might be helpful. In this article, my aim is to provide an analysis of the notion of human dignity in Kant’s works and in Islamic thought and to evaluate how Kant’s approach can offer tools that are relevant to the current debates on dignity in both Western and non-Western traditions.